2012
DOI: 10.5430/jst.v2n3p4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy (SBRT) for non- pathologically diagnosed lung cancer patients

Abstract: Objective: Medically inoperable patients with primary or recurrent lung cancer are increasingly being diagnosed clinically without pathologic confirmation especially for patients with comorbidities that preclude biopsy. The objective of this study is to report the outcomes of medically inoperable patients with unbiopsied primary or recurrent lung carcinoma with SBRT. From 2008From -2011 patients with non-pathologically diagnosed primary or recurrent lung cancer were treated with SBRT. All patients had diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…11 In the study by As expected, we observed minimal toxicities with SBRT and reported no grade three or four toxicities. This is consistent with other studies, 18,19 and highlights the feasibility of SBRT as a curative option in frail patients.…”
Section: F I G U R Esupporting
confidence: 93%
“…11 In the study by As expected, we observed minimal toxicities with SBRT and reported no grade three or four toxicities. This is consistent with other studies, 18,19 and highlights the feasibility of SBRT as a curative option in frail patients.…”
Section: F I G U R Esupporting
confidence: 93%
“…SBRT schedules. For central lung cancer, a total SBRT dose of 55 Gy was delivered by administration of 5 times within 5-7 days, with a treatment interval of 1-3 days (15). Peripheral lung cancer was treated with a total SBRT dose of 48 Gy administered over 4 times within 5-7 days, with a treatment interval of 1-3 days.…”
Section: Methodsmentioning
confidence: 99%